Association Between the Managerial Capacity of Nutrition Personnel and the Achievement of Specific Nutrition Interventions for Stunting Prevention - Rambey, Harris (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: Stunting remains a serious public health issue in Indonesia, with a prevalence rate of 24.4% according to SSGI 2021. Specific nutrition interventions require strong managerial capacity among nutrition personnel. Objective: This study aimed to analyze the relationship between the managerial capacity of nutrition personnel and the achievement of specific nutrition interventions at community health centers (puskesmas) in Deli Serdang Regency. Research Methods: This was a quantitative study with a cross-sectional design. A total of 41 nutrition personnel were selected using proportional random sampling. Data were collected through structured questionnaires and reports on specific nutrition interventions, and analyzed using chi-square tests with a significance level of p<0.05. Results: Most nutrition personnel (63.4%) demonstrated good managerial capacity, and 68.3% achieved high outcomes in specific nutrition interventions. Statistical analysis showed a significant relationship between managerial capacity and intervention achievement (p=0.001), where those with better managerial skills achieved higher intervention targets.Conclusion: Managerial capacity significantly influences the achievement of specific nutrition interventions for stunting prevention. Strengthening managerial skills through continuous training is essential to enhance the effectiveness of nutrition programs at the primary healthcare level.